Biomass-derived versatile activated carbon removes both heavy metals and dye molecules from wastewater with near-unity efficiency: Mechanism and kinetics. (January 2022) - Sherugar, Prajwal; Padaki, Mahesh; Naik, Nagaraj S.; George, Sajan D.; Murthy, Dharmapura H.K.
Abstract: Due to the ever-increasing industrialization, it is critical to protect the environment and conserve water resources by developing efficient wastewater treatment methods. Traditional methods that simultaneously remove heavy metal ions and complex dyes are too expensive and tedious to commercialize. This work demonstrates the versatility, effectiveness, and potential of a biomass-derived adsorbent (from a mangrove fruit of Rhizophora mucronata ) synthesized using a simple route for rapid adsorption of complex dyes and heavy metals with an efficiency of near unity. The cartridges were prepared using activated carbon that removes both dye molecules and heavy metal ions simultaneously from wastewater, corroborating its applicability/feasibility to treat wastewater. Owing to the high surface area (1061.5 m 2 g -1 ) and the pore volume (0.5325 cm 3 g -1 ), the adsorbent showed >99% removal efficiency in just 12 min of exposure to wastewater. The cartridge exhibits >90% removal efficiency of both dyes and heavy metals from its mixed feed solution. The Langmuir and Freundlich models successfully explained the adsorption kinetics. These developed cartridges are versatile, rapid, efficient, and promising candidates for environmental remediation. Graphical abstract: Image 1 Highlights: Highly porous activated carbon (ACs) has been derived from the Mangrove fruit. ACs presents outstanding efficiency in the removal of binary pollutants from water. To accommodate experimental data, two well-known isothermal models are used. Highly efficient cartridge demonstrates >99% removal efficiency from single feed and >90% from binary feed solution.